Tata Kelola Keuangan Desa: Peran Siskeudes, SDM, Kepemimpinan dengan Moderasi Transparansi Anggaran - Wiwit Alfiyatus Safitri; Khoirul Fuad (Yayasan pendidikan dzurriyatul Quran, 2026)
ABSTRACT This study aims to examine the effect of the implementation of the Village Financial System application (Siskeudes), human resource competence, and village head leadership on village financial governance, with budget transparency as a moderating variable. This research employs a quantitative approach using a survey method involving 106 village officials in Grobogan Regency selected through purposive sampling, and the data are analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that the implementation of Siskeudes, human resource competence, and village head leadership have a positive and significant effect on village financial governance, while budget transparency is proven to act as a moderating variable that strengthens the relationship between the independent variables and village financial governance. These findings confirm that the improvement of village financial governance is determined by the optimization of information system utilization, adequate human resource capacity, effective leadership, and budget transparency as a mechanism to enhance public accountability. ABSTRAK Penelitian ini bertujuan untuk mengkaji pengaruh implementasi aplikasi Sistem Keuangan Desa (Siskeudes), kompetensi sumber daya manusia, kepemimpinan kepala desa terhadap tata kelola keuangan desa dengan transparansi anggaran sebagai variabel moderasi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei terhadap 106 perangkat desa di Kabupaten Grobogan yang dipilih melalui pueposive sampling,serta dianalisis menggunakan Structural Equation Modeling (SEM) berbasis Partial Least Square (PLS). Hasil analisis menunjukkan bahwa implementasi Siskeudes, kompetensi sumber daya manusia, dan kepemimpinan kepala desa berpengaruh positif dan signifikan terhadap tata kelola keuangan desa, sedangkan transparansi anggaranterbukti berperan sebagai variabel moderasi yang memperkuat hubungan antar variabel independen dengan tata kelola keuangan desa ditentukan oleh optimalisasi pemanfaatan sistem informasi, kapasitas aparatur yang memadai, kepemimpinan yangefektif, serta keterbukaan informasi anggaran sebagai mekanisme penguatan akuntabilitas publik.